The innovative- technological development of Finland as the formation factor of “knowledge economy” - Pobirchenko, V.; Sharova, O. (Культура народов Причерноморья, 2014)
In this article discusses innovative - technological development as the formation factor of “knowledge economy”, on the example of Finland. Identifying of innovation development preconditions in Finland. The main purpose of the study is: identification of assumptions and factors of innovative and technological development of Finland. To achieve this goal in this article, consistently solved the following problems: 1) an assessment of the factors of innovation and technological development of the country in modern conditions, 2) Studied the characteristics of factors territorial distribution of innovation and technological development, 3) defined territorial differences of innovation and technological development of the regions in Finland and trends of their evolution. This article presents the characteristics of the Finnish national innovation systems, and also characterized the development features of modern Finnish national innovation system. Presenting the indicators that describes the competitive stability of Finnish regional clusters, describing typology in terms of innovative - technological development of the regions. And finally forming of conclusions about innovative - technological activities of the regions in Finland.